Can be in case electronic single rotor unmanned aerial vehicle of crash - QI BING; YU JUN (2017)
The utility model discloses a can be in case electronic single rotor unmanned aerial vehicle of crash, including organism, signal receiver, turncap, sound pressure sensor, acceleration sensor, signal transmission ware, remote switch and directional control button, plastic window is installed in the organism left side, and installs signal receiver on the left of the plastic window below, the flabellum is installed to signal receiver right side top, and installs the turncap on the left of the flabellum below, solar cell panel is installed in turncap below left side, and installs sound pressure sensor below the solar cell panel right side, sound pressure sensor installs the parachute at below left side, and parachute below right side installs acceleration sensor, the support frame is installed to acceleration sensor left side top, and the shaft is installed to support frame left side below. The utility model discloses an install solar cell panel in organism right side top to can follow the duration who improves